Insertion of an Inorganic Barrier Layer as a Method of Improving the Performance of Quantum Dot Light-Emitting Diodes - Yoon, Sang Hyun; Gwak, Dham; Kim, Hong Hee; Woo, Hwi Je; Cho, Jinhee; Choi, Jin Woo; Choi, Won Kook; Song, Young Jae; Lee, Chang-Lyoul; Park, Jongnam; Heo, Kwang; Choi, Young Jin (AMER CHEMICAL SOC, 2019)
Quantum dot light-emitting diodes (QLEDs) are expected to be the basis of next-generation displays and have consequently been extensively investigated with the aim of commercialization. Herein, QLED brightness, efficiency, and lifetime are significantly improved by insertion of an Al2O3 barrier layer via atomic layer deposition (ALD), which effectively suppresses the etching reaction with poly(3,4-ethylenedioxythiophene):polystyrenesulfonate and prevents metal ion diffusion from indium tin oxide (ITO) into the emission layer, thereby effectively reducing the effect of exciton quenching. The above-mentioned suppression of exciton quenching is verified using time-resolved photoluminescence spectroscopy/energy-dispersive X-ray spectroscopy, and a device prepared using four ALD cycles is shown to exhibit increased maximal luminance (39 410 cd/m(2); two times the value achieved without the Al2O3 layer), current efficiency (47.89 cd/A; eight times the value achieved without the Al2O3 layer), and external quantum efficiency (12.89%). In addition, all Al2O3-containing QLEDs feature longer lifetimes than the QLED without Al2O3.